RESPON PERTUMBUHAN TANAMAN SENGON MUDA TERHADAP PUPUK DAN LEGIN, SERTA PERKEMBANGAN PENYAKIT KARAT TUMOR TERHADAP FUNGISIDA DI AREAL EPIDEMI - , ANGGER ADI PERDANA, Dr. Ir. Sri Rahayu, M.P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
At this time, sengon gets a great attention related to the fungi causing gall rust disease, Uromycladium tepperianum. The rust fungus is an obligate parasites, that is able to grow and complete its entire live cycle on the living host. This fungus quickly attacks when sengon plants are still seedling, especially if the plants are in the epidemic areas. This study had been conducted in the epidemic area of gall rust disease in Balong, Umbulharjo, Cangkringan, Sleman. Treatments were arranged in Split-Plot design, consisting of two main plots i.e. without fungicides and with fungicide. The main plots were then divided into six sub-plots, i.e. application compost, SP36, legin, compost+legin, SP36+legin and control. Sample unit for each subplot in each replication was 4 plants of sengon. Layout was arranged in randomized complete block design (RCBD) with four blocks as replications, so overall there are 192 sample units. The results showed that fertilization did not significantly affect plant height growth after 8 weeks in the epidemics area of gall rust disease. Successively, weekly height growth in compost treatment was 0.3-4cm, SP36 0.4-3.8cm, legin 0.3-4cm, compost+legin 0.125-3cm and SP36+Legin 0.2-4.2cm. Disease incidence and severity tended to increase in all treatments until week eight. The disease incidence without fungicide treatment ranged between 48.95%-64.6% and with fungicide 51.6%-63.02%. The disease severity in the leaf and shoots without fungicide treatment ranged from 26.8%-55.5% and 1%-6.25%. The disease severity in the leaf and shoots with fungicide treatment ranged between 27.6%- 53.1% and 1%-3.2%. The disease severity in whole sengon without fungicide treatment ranged from 8.25% -17.82%, and with fungicide 8.5% -16.56%.